Effect of non-Saccharomyces yeasts and lactic acid bacteria interactions on wine flavour. - Du Plessis, Heinrich Wilbur (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.